Reliable determination of the growth and hydrogen production parameters of the photosynthetic bacterium Rhodobacter capsulatus in fed batch culture using a combination of the Gompertz function and the Luedeking-Piret model. Issue 7 (July 2021) - Deseure, Jonathan; Obeid, Jamila; Willison, John C.; Magnin, Jean-Pierre
Abstract: In this study, experimental results of hydrogen producing process based on anaerobic photosynthesis using the purple non-sulfur bacterium Rhodobacter capsulatus are scrutinized. The bacterial culture was carried out in a photo-bioreactor operated in a quasi-continuous mode, using lactate as a carbon source. The method is based on the continuous stirred tank reactors (CSTR) technique to access kinetic parameters. The dynamic evolution of hydrogen production as a function of time was accurately simulated using Luedeking-Piret model and the growth of R. capsulatus was computed using Gompertz model. The combination of both models was successfully applied to determine the relevant parameters (λ, μmax, α and β) for two R. capsulatus strains studied: the wild-type strain B10 and the H2 over-producing mutant IR3. The mathematical description indicates that the photofermentation is more promising than dark fermentation for the conversion of organic substrates into biogas. Abstract : Photofermentation modeling, hydrogen production; Rhodobacter capsulatus; quasi-continuous fermentation